Glucose alert system improves health professional responses to adverse glycaemia and reduces the number of hyperglycaemic episodes in non‐critical care inpatients. Issue 6 (10th April 2018) - Kyi, M.; Wraight, P. R.; Rowan, L. M.; Marley, K. A.; Colman, P. G.; Fourlanos, S.
Abstract: Aim: To investigate the effect of a novel glucose alert system, comprising the Melbourne Glucose Alert Pathway and glucose‐alert‐capable networked blood glucose meters, on nursing and hospital medical officer responses to adverse glycaemia. Methods: A prospective, pre‐ and post‐observational study was undertaken in non‐critical care wards of a tertiary hospital over 4 months ( n =148 or 660 patient‐days). The intervention consisted of two components designed to promote a consistent staff response to blood glucose measurements: (1) a clinical escalation pathway, the Melbourne Glucose Alert Pathway, and (2) networked blood glucose meters, which provide a visual alert for out‐of‐range blood glucose measurement. All consecutive inpatients with diabetes were assessed for diabetes management and capillary blood glucose. The primary outcome was documented nursing and medical staff action in response to episodes of adverse glycaemia (blood glucose >15 mmol/l or <4 mmol/l). Secondary outcomes consisted of glycaemic measures. Results: In response to episodes of adverse glycaemia, nursing action increased (proportion with nursing action: 45% to 73%; P <0.001), and medical action increased (proportion with medical action: 49% to 67%; P =0.011) with the glucose alert system in place. Patient‐days with hyperglycaemia (any blood glucose value >15 mmol/l: 24% vs 16%; P =0.012) and patient‐days with mean blood glucose >15 mmol/l (7.4% vs 2.6%; P =0.005) decreased. There was no difference in hypoglycaemia incidence. Conclusions: Use of a novel glucose alert system improved health professional responses to adverse glycaemia and decreased hyperglycaemia in the hospital setting. What's new?: Lack of health professional response (clinical inertia) to adverse glycaemia is a major barrier to improving diabetes care in the hospital setting. To improve health professional responses, a novel glucose alert system, comprising the Melbourne Glucose Alert Pathway (a clinical escalation and management guide) and glucose alert‐capable networked blood glucose meters, was implemented and evaluated. The glucose alert system improved health professional responses and decreased the number of hyperglycaemic episodes and could be a component of various strategies to improve the care of hospitalized people with diabetes.